2008
DOI: 10.1021/jp800266j
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotubes and Multiwalled Carbon Nanotubes Functionalized with Poly(l-lactic acid): a Comparative Study

Abstract: Spectroscopic (Raman) and gravimetric (acid titration, TGA) techniques were compared to determine the functionalization degree of multiwalled carbon nanotubes (MWNTs) and single-walled carbon nanotubes (SWNTs) with poly(L-lactic acid) (PLLA), following a two-step oxidation/esterification process. After oxidation with HNO 3 , carbon nanotubes (CNTs) were activated with thionyl chloride to the corresponding acid chlorides and then grafted with PLLA. FTIR spectroscopy confirmed the formation of very similarly gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 36 publications
2
43
0
Order By: Relevance
“…In some cases, however, it led to contradictory results. [44] The experimental setup of the Raman experiment might have an influence on the finally obtained spectrum. For example, increasing the laser power density leads to annealing of the structure defects of single-wall carbon nanotubes.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…In some cases, however, it led to contradictory results. [44] The experimental setup of the Raman experiment might have an influence on the finally obtained spectrum. For example, increasing the laser power density leads to annealing of the structure defects of single-wall carbon nanotubes.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…thionyl chloride). [18][19][20] Single step reactions like the in-situ polymerization in the presence of carbon nanofillers or the "grafting to" of functionalized polymers at the carbon nanofillers are the easiest alternatives for the preparation of nanocomposites, however, the control of the extent of functionalization of the nanofillers [21] and their dispersion in the polymer matrix are arduous. [22][23][24] Therefore, the development of simple methods for the controlled functionalization of carbon nanofillers and the posterior compounding with polymer using conventional mixing methods (e.g.…”
Section: Introduction Amentioning
confidence: 99%
“…4 But these polymers usually possess a linear or branched structure, which may lead to relatively unstable dispersions because of the intrinsically weak nature of the interactions between the coating polymer and the CNT. 5 In comparison with a linear or branched structure, a covalently cross-linked structure is a more effective approach to achieving good stability. However, research of using cross-linked polymers as coating layers of CNTs has only rarely been reported.…”
mentioning
confidence: 99%